Catalan Nationalism and Challenges to the Territorial Integrity of Spain - G. I. Volkova (Сравнительная политика, 2016)
At the beginning of the 21st century Spain faced a number of challenges, primarily the growth of separatist sentiments in the regions fraught with the danger of its fragmentation on ethno-national basis. In the context of increased ethno-national mobilization of “small peoples” in Spain one of its most economically developed regions – Catalonia – envisages a rise of the regional identity. Against the backdrop of economic problems generated by the crisis of 2008-2014 the autonomous communities of Spain, including Catalonia, came across the rise of socio-political problems, particularly the growing distance between the society and the central administrative bodies formed in democratic conditions, as well as the two-party administrative system.